Analisis Kesalahan Berbahasa dalam Maharah Qiraah - Fikry Firmansyah; Musta'in Syahri (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to describe the forms of language errors in maharah qira'ah and to find out the factors that cause language errors made by 2B semester students of STAI Ali bin Abi Talib Surabaya. This type of research is descriptive qualitative research with a language error analysis approach. This research was conducted in January 2024 at the Arabic Language Education Study Program of STAI Ali bin Abi Thalib Surabaya with a research sample of 22 students. The data of this study were collected using interview, observation, and documentation techniques. After the data were collected, the data were analyzed using qualitative analysis to describe the forms of language errors and descriptive analysis to determine the factors causing language errors. The results of this study show that the forms of reading errors made by students include errors in Fail; Errors in Jar and Majrur; Errors in Mubtada' and Khobar; Errors in Naibul Fail. Factors causing language errors in maharah qiraah include lack of understanding in Nahwu and Sharaf; lack of practice of the rules of Nahwu and Sharaf; Foreign vocabulary (mufrodat). It is hoped that this research can contribute to efforts to improve the quality of learning maharah qira'ah at STAI Ali bin Abi Talib Surabaya and other educational institutions.